Implementation of Regional Regulation Number 2 of 2024 on the Administration of Business Licensing - Hidayat, Dede Fitra Sarip; Sumaryana, Asep; Buchari, R. Achmad (Borong Newinera Publisher, 2025)
This study aims to analyze the implementation of business licensing policies in Purwakarta Regency, particularly following the enactment of Regional Regulation Number 2 of 2024 concerning the Administration of Business Licensing. This policy is intended to simplify licensing procedures and improve the regional investment climate in alignment with national government policies through Government Regulations Number 5 and 6 of 2021. The study employs a qualitative descriptive method with a case study approach in Purwakarta Regency. Data collection techniques include literature review, field studies through interviews, observation, and document analysis. Data validity is tested using triangulation techniques. The research findings, based on the theoretical framework of Puentes-Poloche et al. (2023) on e-government and digital governance policy studies, indicate that although the licensing process is conducted digitally through the Online Single Submission (OSS) system and online licensing applications (GASPOL and SIMBG) have been implemented, several challenges remain. These include limited understanding of the digital system among business actors—particularly MSMEs—insufficient infrastructure, and coordination barriers with relevant agencies. On the other hand, continuous improvement efforts have been made by the local government, such as enhancing human resource capacity and conducting public outreach on the policy. This study recommends the need for stronger synergy between central and local governments, as well as the strengthening of institutional capacity among local agencies to support the effective implementation of business licensing policies at the regional level.